A novel high-pressure phase of ScN5 with higher stability predicted from first-principles calculations. (10th September 2021) - Wei, Shuli; Liu, Zhipeng; Guo, Yanhui; Sun, Haiyang; Chang, Qiang; Sun, Yuping
Abstract: For binary compounds of Sc–N, the stable structures and stoichiometries were studied from ambient condition to high pressure of 100 GPa, adopting CALYPSO method. The newly predicted P 21 /c-ScN5 compound was more energetically stable under high pressure P = 62 GPa comparing with the three previously reported phases of P 1-ScN5, Cm -ScN5 and C 2/ m -ScN5 . Furthermore, the high-pressure phase of P 21 /c-ScN5 was dynamically stable at ambient condition, so the ambient-pressure recovery is possible. In this paper, the study suggested that the energetic polynitrides can be obtained in transition metal nitrides under high pressure. And we identified one novel 3D extended puckered poly-nitrogen network in the P 21 /c-ScN5 structure, which is similar to the C 2/ m -ScN5 . The decomposition of P 21 /c-ScN5 to ScN and N2 under ambient pressure was estimated to release 5.02 eV energy per formula unit (f.u.), corresponding to 4.19 kJ g −1 in energy density, which was expected to be highly exothermic. The present results can conduce to obtain more polynitrogen forms and theoretically encourages experimental discovery in these promising materials.